2013
DOI: 10.4028/www.scientific.net/kem.551.118
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Ti-6Al-4V Alloy via Oxygen Solid Solution Strengthening for Aerospace & Defense Applications

Abstract: The high cost of titanium has historically prevented widespread use in military ground vehicles. Two strategies to make this material more cost effective and viable are to reduce the cost of titanium armors or to improve the ballistic performance of titanium and reduce the amount of material required. This paper investigates the latter strategy. Mixtures of titanium powders and TiO2 particles were employed as starting materials and consolidated by spark plasma sintering (SPS) and hot extrusion. The content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…ubiquitous alloying elements). 1,2) Titanium alloys exhibit a remarkable improvement in strength even with small additions of oxygen, an interstitial solid solution element in Ti. Although the elongation to failure decreases with increasing the oxygen addition, it has been confirmed that this effect approaches a limit at approximately 0.1 mass% O content.…”
Section: Introductionmentioning
confidence: 99%
“…ubiquitous alloying elements). 1,2) Titanium alloys exhibit a remarkable improvement in strength even with small additions of oxygen, an interstitial solid solution element in Ti. Although the elongation to failure decreases with increasing the oxygen addition, it has been confirmed that this effect approaches a limit at approximately 0.1 mass% O content.…”
Section: Introductionmentioning
confidence: 99%
“…[88] They occupy the octahedral interstices and expand the crystal lattice, particularly along the c-axis, leading to an increased c/a ratio as shown in Figure 11. [101,105,118,[130][131][132][133] Solute N has a larger atomic radius than O and thereby exhibits a faster increase in c/a Figure 10. Failure profile of TiMMCs reflecting the strong reinforcement-matrix bonding: a) in Ti-6Al-4V strengthened with TiB whiskers, and b) in Ti refinforced with multi-layer graphene (MLG).…”
Section: Solid Solution Strengtheningmentioning
confidence: 99%
“…Machinability of Ti-6Al-4V is of immense importance due to its widespread use in many applications especially in biomedical 1 , automotive 2 , shipbuilding 3 , micro-electromechanical systems 4 and defense industry 5 . Machinability of Ti-6Al-4V is rated as challenging 6 , 7 and poor due to very low thermal conductivity, high chemical reactivity and low modulus of elasticity due to which it is considered as difficult-to-cut material and rapid tool wear is experienced during conventional machining methods 8 .…”
Section: Introductionmentioning
confidence: 99%